Conviction in an Optional Society : Pentecostal / Charismatic Christianity and Religious Pluralism - Behera, Marina Ngursangzeli (Book collections on Project MUSE., 2020)
Today, more than ever, we are challenged to think on a larger scale and act in common pursuit with regard to social challenges, our convictions and public engagement. What bearing do these contexts have on our communication and practical action? How can we live responsively and remain faithful to our fundamental beliefs? The papers presented here suggest constructive answers.